Ikonografia wcielenia w sztuce wczesnoromańskiej i romańskiej na wybranych przykładach scen Bożego narodzenia - Mazurczak, Urszula (Vox Patrum, 2000)
In the art the Theme of Incarnation was illustrated in a rich scene repertiore creating its prototypes at the early Romanesque and Romanesque period. It was also the time of dynamically forming motifs in the art that defined the Gothic art and to a high degree modern one. In the fine arts such a model of Incarnation was made by Nativity scene.